2016
DOI: 10.17113/ftb.54.04.16.4323
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antioxidant Activity of Silybum marianum Extract and Its Protective Effect against DNA Oxidation, Protein Damage and Lipid Peroxidation

Abstract: SummaryAntioxidant properties of ethanol extract of Silybum marianum (milk thistle) seeds was investigated. We have also investigated the protein damage activated by oxidative Fenton reaction and its prevention by Silybum marianum seed extract. Antioxidant potential of Silybum marianum seed ethanol extract was measured using diff erent in vitro methods, such as lipid peroxidation, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing power assays. The extract signifi cantly decreased DNA damage caused by hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
4
5
1
Order By: Relevance
“…(2014) value as (20.92 mg/g). Moreover, Serce et al., (2016) finding are supported current results that milk thistle contained phenolic contents as 620.0 µg/g in ethanol extract. The finding of Pereira et al., (2014) are synchronized 23.26 mg/g with the current results.…”
Section: Resultssupporting
confidence: 73%
“…(2014) value as (20.92 mg/g). Moreover, Serce et al., (2016) finding are supported current results that milk thistle contained phenolic contents as 620.0 µg/g in ethanol extract. The finding of Pereira et al., (2014) are synchronized 23.26 mg/g with the current results.…”
Section: Resultssupporting
confidence: 73%
“…High antioxidant activities were examined within all size fractions of this species; however, the A250 fraction had the highest activity, which reached 101.95 mg AAE/g flour. The antioxidant activity of milk thistle seeds was previously given in correlation with bioactive flavonolignans (silymarin complex) [48,54]. Moreover, our data suggested the accumulation of antioxidants in the surface structure of milk thistle seeds.…”
Section: Functional Characteristics Of Oilseed Cake Flourssupporting
confidence: 64%
“…Seed extracts of S. marianum collected from 30 different regions of Greece have been reported to have antioxidant potential [21]. It was reported that ethanol and petroleum ether extract of the seeds of S. marianum collected from Turkey were the antioxidant potential [22]. In China, ethanol extracts of leaf, man stem, root, fruit receptacle and pappus of S. marianum were used.…”
Section: Antioxidant and Oxidant Potentialmentioning
confidence: 99%